Establishing referance intervals for haematological parameters, soluble serum transferrin receptor and serum transferrin in a tertiary hospital in Malaysia - Hemalatha, S.; Thatcheiany, K.; Pavai, S. (2014)

(untitled)
Clinical laboratory testing is an integral part of diagnosis, treatment and prognosis that ensures quality and effective healthcare. Factors like genetics, dietary intake, gender, age, level of physical activity, altitude above sea level etc. can alter biochemical and haematological parameters in a population Variation can also occur based on the instrument or methodology being used. Thus it is pivotal for laboratories to establish their own reference intervals specific for their population. In our laboratory we have been interpreting CBC results based on the reference value established for the western population. In the context above, we decided to establish our own reference value by studying healthy Malaysian adults. Iron deficiency is also a common clinical problem in our population. Its distinction from anaemia secondary to infection, inflammation or malignancy remains a clinical challenge. The conventional laboratory tests of iron status are influenced by several factors but additional markers such as serum transferrin and serum soluble transferrin receptor helps in better evaluation of iron status. The aim of this study was to determine reference interval for haematology parameters and serum iron markers that includes serum soluble transferrin receptor and serum transferrin.